2017
DOI: 10.21608/hjsc.2017.6395
|View full text |Cite
|
Sign up to set email alerts
|

Ex vitro Performance and Genetic Stability of Strawberry Plants Derived from Different in Vitro Propagation Methods

Abstract: Ex vitro experiment was conducted at the greenhouse and nursery facilities of the Plant Tissue Culture Laboratory of Department of Horticulture, Faculty of Agriculture, Suez Canal University during the period 2009-2012. Strawberry ex vitro growth performance of tissue culture-derived plants from different propagation methods (meristem, direct regeneration and callus-derived plants) were examined with standard runner-propagated mother plants based on morphological traits and genetic analysis using RAPD. Ex vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…In order to assess the genetic variability of berry plants, the RAPD and ISSR markers are most frequently used. In several research papers, the use of AFLP, SSR, and SRAP markers was also reported [17,19,21,25,[61][62][63]65,[70][71][72]. AFLP analysis proved to be more reliable and sensitive than other methods not only in our research, but also in the studies of Lanham and Brennan [21] and Costa and co-workers [31].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In order to assess the genetic variability of berry plants, the RAPD and ISSR markers are most frequently used. In several research papers, the use of AFLP, SSR, and SRAP markers was also reported [17,19,21,25,[61][62][63]65,[70][71][72]. AFLP analysis proved to be more reliable and sensitive than other methods not only in our research, but also in the studies of Lanham and Brennan [21] and Costa and co-workers [31].…”
Section: Discussionsupporting
confidence: 72%
“…Using both marker systems, the lowest genetic variability was detected in Hinnonmaki Rot and the highest in Invicta. Mohamed and co-workers [61] assessed the genetic stability of in vitro-derived plants of several strawberry cultivars using RAPD markers. The study also revealed that the frequency of genetic variation depends on the cultivar studied; plants of Tudla, depending on the culture conditions, showed polymorphism within 2.86-11.77%, while the variability in the cultivar Festival ranged from 10.35 to 30.77%.…”
Section: Discussionmentioning
confidence: 99%
“…Однако внедрение в производство биотехнологических методов повлекло за собой и новый ряд принципиальных проблем. Достаточно скоро в научной литературе стала появляться информация о том, что у растений, полученных in vitro, периодически наблюдаются аномалии роста и развития [2,3]. В результате возникло предположение о дрейфе генотипа и, как результат, возможной генетической неоднородности получаемого материала [4].…”
Section: Introductionunclassified